Effect of time in plasma electrolytic oxidation process on titanium substrate with addition nano alpha alumina powder in electrolyte and investigate wear behavior of coating - Sarbishei, S.; Faghihi-Sani, M.A.; Mohammadi, M.; Einkhah, F. (International Conference on Plasma Surface Engineering, 2013)
Titanium and its alloys have wide applications in industry and recently researches have been expanded in this area. The main reasons are unique features of titanium such as biological behavior, corrosion resistance and high strength to weight ratio. The fundamental problem of titanium is low wear resistance that leads to be worn in industrial applications. Plasma electrolytic oxidation (PEO) is a novel method to create ceramic coatings on metals and improve wear resistance. Base of this method is similar to electrochemical coating methods with difference the high voltage discharge phenomenon. In this research hard nano alpha-alumina particles (hardness of 9 Mohs) were added to the electrolyte for improving wear properties of titanium.